The Collegiate Learning Assessment : setting standards for performance at a college or university - Hardison, Chaitra M. (Technical report (Rand Corporation), 2009)
"This report describes the application of a technique for setting standards on the Collegiate Learning Assessment (CLA), a measure of critical thinking value-added at higher education institutions. The goal of the report is to illustrate how institutions can set their own standards on the CLA using a method that is appropriate for the unique characteristics of the CLA."--Provided by publisher